Successful interruption of seasonal influenza transmission under the COVID-19 rapid response in Zhejiang Province, China. (December 2020) - Cheng, W.; Yu, Z.; Liu, S.; Sun, W.; Ling, F.; Pan, J.; Chen, E.
Abstract: Objectives: The objective of this study was to evaluate whether the non-pharmaceutical interventions (NPIs) introduced to curb the spread of coronavirus disease 2019 (COVID-19) also interrupted the transmission of influenza. Study design: This is a descriptive epidemiological study. Methods: Data on changes in the number of reported influenza cases, number of influenza-like illness (ILI) visits, ILI percentage and influenza virus positivity were compared between the first 18 weeks of 2020 and the same period of 2019. Results: The changes in the weekly average number of influenza cases were statistically significant between 2020 and 2019 (−4319 vs −525 per week; P < 0.05). The slopes of regression lines for the number of ILI visits were also statistically significant between 2020 and 2019 (−911 vs −98 per week; P < 0.05). Conclusions: This study found that the prevalence of influenza was substantially decreased when NPIs were implemented for the containment of COVID-19. Highlights: The prevalence of influenza was substantially decreased when non-pharmaceutical interventions were implemented for the containment of coronavirus disease 2019. Changes in the weekly average number of influenza cases were statistically significant between 2020 and 2019 (−4319 vs −525 per week; P < 0.05). Changes in the number of influenza-like illness visits were also statistically significant between 2020 and 2019 (−911 vs −98 per week; P < 0.05).